EXPLORING THE PHILOSOPHY OF LANGUAGE: SCOPE, HISTORY, AND ITS CONNECTIONS WITH CULTURE AND LITERATURE - Solo, Lenny; Nuruddin (Department of English Education, Universitas Panca Sakti Bekasi, 2024)
This research focuses on the importance of the philosophy of language in understanding the relationship between language, reality, culture, and human communication. This study was conducted using a qualitative approach with a descriptive-analytical approach. Data was collected through literature studies and analysis of primary literature in the philosophy of language, covering theories of epistemology, ontology, and axiology in the context of language. Philosophy, which comes from the Greek words